Identifying muon sites "by eye" in KPF6 and KBF4 - Wilkinson, JM; Lang, F; Baker, PJ; Cottrell, SP; Blundell, SJ (IOP Publishing, 2023)
Molecular magnets are one of the key research themes of µSR, but locating the muon stopping site in these compounds using density functional theory is often very challenging as their unit cells tend to contain a very large number of atoms. Nevertheless, many molecular magnets contain the [PF6]− and [BF4]− molecular ions, which, due to their fluorine nuclei, produce a distinctive µSR spectrum, which can give information about the muon stopping site. This paper details the calculation of the muon sites in the much simpler materials KPF6 and KBF4, providing insights which can be applied to situations where these molecular ions are found in complicated molecular magnets.